Harmonization of Rice Production Policy and Rice Trade Policy in Indonesia - Vadilaksono, Muhammad Ivan; Syaukat, Yusman; Widyastutik (Jurnal Manajemen & Agribisnis, 2023)
Indonesia is the world's fourth most populous country, trailing only China, India, and the United States, with a population of 276,361,788 people. Efforts to fulfill the demand for rice as a staple food are concerning. The policies established by the Ministry of Agriculture and the Ministry of Trade do not match. The Ministry of Agriculture carries out a pro-rice production policy. The Ministry of Trade carries out a pro-rice import policy. This study included both descriptive and quantitative analysis. The type of data used in this research is annual time series secondary data with a research period from 1980 to 2020. The model used in this study was developed using the Two Stage Least Squares (2SLS) approach. The results showed that the Ministry of Agriculture's goal was to boost output, but this might lead to overstock and consequently reduce rice prices, according to the Ministry of Trade. The Ministry of Trade's rice import policy has always been withheld by the Ministry of Agriculture because, according to the Ministry of Agriculture, imports will lower the rice price, reducing farmers' income. This shows that production and trade policies are not well-suited. Production policies, with an average annual increase of 2%, outperform trade policies, with an average annual increase of 141%. Keywords: rice, food, production policy, trade policy, harmony